Decentralized Finance to Improve the Performance of Centralized Finance - KARAULOVA, Yuliya (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The urgency of the problem under investigation is conditioned by the need to find mechanisms that contribute to maintaining a balance in the process of realizing increasingly complex tasks that state faces, with a lower level of budgetary opportunities. The article is aimed at developing the theoretical foundations of finance and the mechanism for mobilizing financial resources necessary for the region in implementing strategic tasks by means of involving decentralized finances in the process of implementation of state programs by the subject of measures to achieve the synergistic effect obtained in their interaction with centralized finances contributing to improving the efficiency of public finances. The article considers theoretical aspects of finance, and formulates the necessity of application and introduction in practice of the accumulated scientific potential in the processes of solving state problems; makes generalization of the main problems in the sphere of centralized finance management in the subjects of the Russian Federation; presents the algorithm of practical application of the model of the mobilization mechanism of centralized and decentralized financial resources in the process of implementing the state program designed to increase the effectiveness of public finances in the region, using the example of the Samara region. The materials of the article can be useful and successfully implemented in practice in other regions of the Russian Federation.